Athenry Dominican Priory, north chancel wall, sedilia, jamb - O'Donovan, Danielle (My University, 2008)
Moulding from intrados comprises: chamfer, roll-and-fillet, roll, partial roll.
Sedilia
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Dominican; Church furniture.; Late Medieval; roll-and-fillet moldings; roll moldings